Application of biophysical methods for improved protein production and characterization: A case study on an high‐temperature requirement A‐family bacterial protease. (22nd November 2022) - Ronzetti, Michael; Baljinnyam, Bolormaa; Jalal, Ishrat; Pal, Utpal; Simeonov, Anton
Abstract: The high‐temperature requirement A (HtrA) serine protease family presents an attractive target class for antibacterial therapeutics development. These proteins possess dual protease and chaperone functions and contain numerous binding sites and regulatory loops, displaying diverse oligomerization patterns dependent on substrate type and occupancy. HtrA proteins that are natively purified coelute with contaminating peptides and activating species, shifting oligomerization and protein structure to differently activated populations. Here, a redesigned HtrA production results in cleaner preparations with high yields by overexpressing and purifying target protein from inclusion bodies under denaturing conditions, followed by a high‐throughput screen for optimal refolding buffer composition using function‐agnostic biophysical techniques that do not rely on target‐specific measurements. We use Borrelia burgdorferi HtrA to demonstrate the effectiveness of our function‐agnostic approach, while characterization with both new and established biophysical methods shows the retention of proteolytic and chaperone activity of the refolded protein. This systematic workflow and toolset will translate to the production of HtrA‐family proteins in higher quantities of pure and monodisperse composition than the current literature standard, with applicability to a broad array of protein purification strategies.